Influence of cryopreservation media on fertilization rate and post-thaw characteristics of tiger (Panthera tigris ssp.) spermatozoa - Shelley E.S. Sandmaier; Jason R. Herrick (Theriogenology Wild, 2025)
There is a growing need for the development of assisted reproductive technologies to manage tiger populations under human care. Artificial insemination has been successful in tigers and other felid species but is ultimately reliant on the quality of the sperm sample. Cryobanking of tiger spermatozoa can aid in these efforts, but viability is reduced after thawing when compared to fresh samples. The current study tested new cryopreservation media with the goal of improving post-thaw viability and motility of tiger spermatozoa. Semen was collected by electroejaculation from 13 tigers and one or more treatments (TEST egg yolk buffer, soy, soy + glutamine, and soy + trehalose) were chosen for cryopreservation of each sample. Motility, acrosome integrity, and embryo development following heterologous in vitro fertilization (IVF) of domestic cat oocytes were evaluated to determine the effectiveness of each treatment. After thawing, none of the soy-based media improved upon these characteristics when compared to TEST egg yolk buffer. Despite low (average = 20 %) motility after thawing, all samples were capable of producing embryos via IVF. Results from this study indicate that both TEST and soy-based media can be used to cryopreserve tiger spermatozoa. However, there is still much room for improvement of sperm cryopreservation in this species.